Inklusion als schulischer Transformationsprozess Möglichkeiten und Grenzen der indikatorengestützten Darstellung des Gemeinsamen Lernens auf kommunaler und Einzelschulebene - Tegge, Dana (Interdisziplinäre Beiträge zur Inklusionsforschung, 2020)
With the development of inclusive schools comes a broad range of new challenges within the whole German education system. According to the different responsibilities in the educational governance of the German system, not only the state level but also the district level has an important role in the reorganization process towards an inclusive school system. This doctoral thesis thus aims at developing a set of educational indicators at district and individual school level that provides information about the inputs, processes and outputs of inclusive schooling, i.e. conditions and school organizational aspects such as experience in dealing with heterogeneity (special educational needs, migration, gender, etc.). Thereby it can also provide a foundation for continuous, largely data-based observation and analysis of the implementation process of school inclusion. This kind of monitoring can inform both German educational policy and the public regarding contexts, process characteristics, outcomes and benefits of inclusive schooling. The main question of the thesis thus is: What indicators can be identified to describe and reflect developments in the implementation of an inclusive school system at the district level? This is addressed by a three-step analysis, exemplified by a typical German municipality in North Rhine-Westphalia. (1) Starting with an analysis of available school statistics in the period from 2007 to 2015 (2), the results are supplemented by a quantitative school-leadership survey in 2016 (3). A synthesis of the given results marks the last step with a characterization of the transformation process at school and district level. The framework of indicators is meant to identify general problems and offer an empirical foundation for the information on inclusive schooling in German municipalities, thus providing valid governance knowledge for a holistic, coherent educational management as well as contributing to improve the quality of inclusive education at district level. (DIPF/Orig.)